The The Effects of Realia Towards Descriptive Writing Ability at Seventh Grade Students of SMP PGRI Kramatwatu - Wulandari, Ratih Ayu; Safira, Meli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
This study was aimed to find out the effect of realia on descriptive writing ability at the seventh-grade students of SMP PGRI Kramatwatu. This is a quantitative study with a quasi-experimental design in which the researchers applied a non-equivalent control group design. The research sample was 40 students taken by using purposive sampling technique. In collecting data, researchers used a written test. The results of this study indicated that (1) the results of the pre-test t-count is 3.469 > t-table 2.024 or H1 is accepted, which means that there was a difference of students’ descriptive writing ability between the experimental class and the control class before the treatment, (2) the results of the post-test t-count is 2.173 > t-table 2.024 or H1 is accepted, which means there was a difference of students’ descriptive writing ability between those who were taught by using realia and those who were taught by using conventional media (picture). It could be concluded that realia media had a positive effect towards students’ descriptive writing ability at the seventh grade of SMP PGRI Kramatwatu.